The Importance of Developmental Centers in Preparing Preschool Children for School - Fozilova Odinakhan Nabiyevna; Jaloliddinova Maftunakhan Mahmudjon kizi (Genius Journals, 2023)
In the article, the further improvement of the preschool education system, the study of advanced foreign experiences in the field of preschool education organization, innovative methods and effective pedagogical practices in the field of education and upbringing of preschool children, development in quality preparation of children for school education the importance of centers and the essence of the organization of development centers are discussed.
Keywords: Preschool education system; development centers; critical thinking; independent